The Influence of the SAVI Learning Model on the Poetry Reading Skills of Class X Students of SMAN 1 Grogol Kediri - Amelia Puspitasari; Andri Pitoyo; Moch. Muarifin (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to: 1) describe the posttest results of poetry reading skills of class X students of SMAN 1 Grogol Kediri without the SAVI learning model; 2) describe the posttest results of poetry reading skills of class X students of SMAN 1 Grogol Kediri with the SAVI learning model; 3) whether or not the SAVI learning model has an effect on poetry reading skills of class X students of SMAN 1 Grogol Kediri. This study uses a quantitative descriptive method through a quasi-experimental design with a pretest posttest control group design. This study took place at SMAN 1 Grogol Kediri in the 2025/2026 academic year. The population of this study was 36 class X-1 students and 36 class X-4 students who took the poetry reading skills pretest, who took the poetry reading skills learning, and who took the poetry reading skills posttest. The sample was determined at 62 students with the same number per class; drawn by simple random sampling without replacement. Data on poetry reading skills were collected using a poetry reading performance test instrument. Poetry reading skill data were analyzed using descriptive statistics to determine poetry reading skills and inferential statistics, namely the independent sample t test to calculate the effect of the SAVI model on poetry reading skill learning outcomes. The data analysis technique used the SPSS version 27 application with a significance value (2-tailed) of 0.001 <0.05. The results of the study: 1) the posttest results of poetry reading skills of class X students of SMAN 1 Grogol Kediri without the SAVI learning model were in the low category; 2) the posttest results of poetry reading skills of class X students of SMAN 1 Grogol Kediri with the SAVI learning model were in the high category; 3) the SAVI learning model on poetry reading skills of class X students of SMAN 1 Grogol Kediri because the t value had a sig. 0.00 <0.05.